The Evolution of Job Displacement in the Age of AI and Automation: A Bibliometric Review (1984–2024) - Subaveerapandiyan A.; Shimray Somipam R. (Open Information Science)
This study presents a comprehensive bibliometric analysis of the scientific literature about artificial intelligence (AI), automation, and job displacement from 1984 to 2024. Utilizing the Scopus database, 225 relevant documents were retrieved and analysed using R Studio and VOSviewer. The analysis reveals significant trends in publication growth, citation metrics, and collaborative networks among researchers and institutions. Notable findings indicate a marked increase in research output during key technological advancements, highlighting the evolving discourse surrounding the implications of AI and automation on the workforce. This study identifies prevailing themes within the literature through keyword analysis and explores the interconnectedness of research contributions across various domains. This bibliometric review aims to provide a foundational understanding of the current landscape and future directions in studying AI, automation, and job displacement.